PEMERIKSAAN TEKANAN DARAH, GULA DARAH DAN ASAM URAT SECARA RUTIN MASYARAKAT MALINO TERBEBAS DARI PENYAKIT DEGENERATIF - Muliana Hafid; Andi Muhammad Farid; Muh. Aris; Sulastri; Andi Armisman Edi Paturusi; Deniyati (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2025)
Non-Communicable Diseases (NCDs) are caused by progressive changes in cell and tissue function, such as coronary heart disease, diabetes mellitus, hypertension, cancer, and osteoporosis. Degenerative diseases such as diabetes mellitus, hypertension, and gouty arthritis are major health problems in society. One preventive measure is early detection through routine health checks, especially blood sugar and uric acid level checks. This community service activity aims to increase public awareness in preventing degenerative diseases through health checks and education. The methods used are direct examinations (random blood sugar and uric acid level screening), blood pressure checks, and health education. The results of the activity showed community participation of 85% of the total invitations, with 32% of participants having above-normal blood sugar levels, and 28% of participants having high uric acid levels. After being given education, 90% of participants stated that they would undergo re-examination and adopt a healthy lifestyle. This activity has a positive impact in increasing public awareness, especially in Malino, about the importance of regular health checks as a step to prevent degenerative diseases